Pengaruh Harga dan Kualitas Layanan Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Sebagai Variabel Intervening Jasa Online Maxim - Delvia Safitri; Annur Fitri Hayati (Jurnal Ecogen, 2022)
This study aims to determine and analyze the effect of price and service quality on customer loyalty through customer satisfaction as an intervening variable (study of consumers at Padang State University students. This type of research is causative research. The population in this study were Padang State University students on Maxim's online service and the determination of the number of samples using the Cochran formula as many as 97 respondents. This study uses a purposive sampling technique with the consideration that consumers have used Maxim's online services. The data used is the type of primary data obtained through distributing questionnaires to Padang State University students with predetermined criteria. The analytical method used is path analysis.The results of this study indicate that (1) price has a significant effect on customer loyalty (2) service quality has a significant effect on customer loyalty (3) price has a significant effect on customer satisfaction (4) service quality has a significant effect on customer satisfaction (5) satisfaction customer has a significant effect on customer loyalty (6) price has a significant effect on loyalty with customer satisfaction as an intervening variable for Maxim online services at Padang State University students (7) service quality has a significant effect on loyalty with customer satisfaction as an intervening variable for Maxim online services in Padang State University students.Keywords: price, service quality,customer loyalty, and customer statisfaction